2021
DOI: 10.1186/s13033-021-00487-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors associated with depression in the hill tribe population aged 40 years and older in northern Thailand

Abstract: Background Depression is globally recognized as a major mental health problem in all age categories, particularly among those living in poor economic conditions and with low levels of education, including the hill tribe people in northern Thailand. Methods This cross-sectional study aimed to estimate the prevalence of depression and determine the factors associated with depression in the hill tribe population aged 40 and over in northern Thailand. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 18 publications
0
25
0
1
Order By: Relevance
“…12 The proportion of depression among this group is comparable to other vulnerable populations such as ethnic or gender minorities. 13,14 Factors related to Thai medical student depression include academic performance, learning environment, relationship, and community, as well as individual vulnerabilities such as motivation and self-care. 7,9 According to the Thai medical education curriculum, the first clinical year of all students begins at the fourth year, which coincides with the greatest prevalence of depressive disorders and suicidal ideation in Thai students.…”
mentioning
confidence: 99%
“…12 The proportion of depression among this group is comparable to other vulnerable populations such as ethnic or gender minorities. 13,14 Factors related to Thai medical student depression include academic performance, learning environment, relationship, and community, as well as individual vulnerabilities such as motivation and self-care. 7,9 According to the Thai medical education curriculum, the first clinical year of all students begins at the fourth year, which coincides with the greatest prevalence of depressive disorders and suicidal ideation in Thai students.…”
mentioning
confidence: 99%
“…Despite the fact that 52% of Thailand’s people live in urban areas, which provide a facility for support in the event of depression, there are only about 882 psychiatrists in the country, which is insufficient to assist the entire population [ 8 , 9 ]. Furthermore, there have been numerous reports which indicated that a significant number of people in rural areas are underdiagnosed with depression [ 10 , 11 ]. A study reported that the prevalence of depression in the elderly in rural areas was as high as 18.5% [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study reported that the prevalence of depression in the elderly in rural areas was as high as 18.5% [ 10 ]. Another study revealed that the prevalence of depression among Thai hill tribe residents is approximately 39.1% [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under the crisis of the COVID-19 pandemic, IPV has increased its impact on both the frequency and level of violence [ 4 ]. Those who live in poverty [ 13 ], are minorities [ 14 ], and have a poor education [ 3 , 15 ] are particularly vulnerable to IPV.…”
Section: Introductionmentioning
confidence: 99%